A qualitative study exploring the education provided to midlife women with persistent post-concussion symptoms - Jaynee Lie; Katherine A. Tamminen (Cogent Psychology)
Purpose Between 20% and 40% of adults with a concussion experience a recovery period longer than the expected 3-month timeframe, which has been coined the term persistent post-concussion symptoms (PPCS; Cnossen et al., Popov et al.). Females (Kerr et al.) and older adults over the age of 40 are more likely to experience PPCS (Ryan & Warden). Early education plays a vital role in concussion recovery and preventing the onset of PPCS (Rickards et al.). However, there are few studies that have focused explicitly on the education that patients with a concussion and PPCS are receiving. Therefore, the purpose of this study was to explore how the education given to midlife women with an mTBI affected their experiences with PPCS.Method Five female participants (between the ages of 39 and 50) took part in one-on-one semi-structured online interviews to share their experiences with their concussion and PPCS and the education they received related to their injury. The interview transcripts were analyzed using thematic analysis to identify main themes regarding their experiences.Results The main themes identified related to (a) the variety and variability of education received, (b) the timing of the education in relation to their concussion diagnosis, and (c) the impact of the education and the process of getting information about PPCS.Implications The results indicate a need for more research and proper education delivery on concussion and PPCS management among health care professionals to improve the experiences and recovery of patients with an mTBI.